The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0085446
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance and Molecular Mechanism of ATP-Binding Cassette Subfamily C Member 4 in Resistance to Neoadjuvant Radiotherapy of Locally Advanced Rectal Carcinoma

Abstract: BackgroundMechanism of radioresistance in rectal carcinoma remains largely unknown. We aimed to evaluate the predictive role of ATP-binding cassette subfamily C member 4 (ABCC4) in locally advanced rectal carcinoma and explore possible molecular mechanisms by which ABCC4 confers the resistance to neoadjuvant radiotherapy.MethodsThe expression of ABCC4 and P53 mutant in biopsy tissue specimens from 121 locally advanced rectal carcinoma patients was examined using immunohistochemistry. The factors contributing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…49 The significant association observed between sensitivity to neoadjuvant RT and downregulation of ABCC4 (MRP4) indicates a possible role of this protein as a predictive biomarker, 50 and the correlation between high ABCC4 expression and shorter DFS makes it a good biomarker of poor outcome in LARC. 51 Finally, the negative effect on pathological response of aberrant expression of MRP3, another member of this family, was recently shown by Yu et al in 144 pretreatment rectal biopsies from patients treated with NCRT. 52 With regard to protein microarray technologies, Mammano et al published an interesting report in 2012 based on a new method for quantitative multiplexed analysis of protein signaling activation.…”
Section: Protein Expressionmentioning
confidence: 92%
“…49 The significant association observed between sensitivity to neoadjuvant RT and downregulation of ABCC4 (MRP4) indicates a possible role of this protein as a predictive biomarker, 50 and the correlation between high ABCC4 expression and shorter DFS makes it a good biomarker of poor outcome in LARC. 51 Finally, the negative effect on pathological response of aberrant expression of MRP3, another member of this family, was recently shown by Yu et al in 144 pretreatment rectal biopsies from patients treated with NCRT. 52 With regard to protein microarray technologies, Mammano et al published an interesting report in 2012 based on a new method for quantitative multiplexed analysis of protein signaling activation.…”
Section: Protein Expressionmentioning
confidence: 92%
“…This study provided the first experimental evidence that MRP4 and cAMP extrusion may represent a new potential target for differentiation therapy. Moreover, several clinical studies using tumor genome sequencing showed MRP4 expression as a prognosis marker in esophageal [ 15 ], gastric [ 16 ], rectal [ 17 ], lung [ 18 ], ovarian [ 19 ] and prostate [ 20 ] cancer as well as in neuroblastoma [ 21 ]. Furthermore, current evidence also supports that MRP4 expression may represent a relevant pharmacological target [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…ABCC4 confers cells resistance to cytotoxic complexes, protects important tissues from aberrant biological damage and at the same time affects drug metabolism in cells, resulting in drug resistance. Significant association between downregulation of ABCC4 and sensitivity to neoadjuvant chemo-radiotherapy, as well as between low ABCC4 expression and longer disease-free survival in rectal cancer patients has been demonstrated 18 , 19 , indicating that ABCC4 might be a possible predictive biomarker for the efficacy of chemotherapy in CRC. Recent reports demonstrate that the expression of ABCC4 can be attenuated by miR-124a, miR-125a, miR-125b, miR-143, and miR-506 13 , 20 .…”
Section: Discussionmentioning
confidence: 99%